Elimination of pretransfusion RhD typing at Mackay Memorial Hospital, Taiwan—30‐year experience (1988–2017). Issue 2 (20th September 2020) - Lin, Marie
Abstract : Background: The frequency of the RhD negative (D‐) phenotype among the population of Taiwan is only 0·34% and so anti‐D is a relatively rare antibody. Routine pretransfusion D typing of patients at Mackay Memorial Hospital (MMH) was discontinued in 1988, and this report is a look back and retrospective evaluation over 30‐years (1988–2017). Study Design and Methods: The incidence of anti‐D among patients at MMH during the periods 1984–1988 (when D typing was performed) and 1988–2017 (when D typing was not performed) was reviewed. Also, the incidence of anti‐D among both MMH patients and voluntary blood donors at the Taiwan Blood Foundation was compared. The importance of anti‐'Mi a ' in Taiwan is also discussed. Results: The incidence of anti‐D relative to other Rh antibodies among MMH patients when D typing was performed and D typing not performed has remained relatively unchanged (5%). The frequencies of anti‐D and anti‐'Mi a ' among 38 537 patients who were transfused at MMH during 2008–2017 were found to be 0·06% and 2·6%, respectively. During the same period, among 3 510 131 blood donors at Taiwan Blood Foundation, the frequencies of anti‐D and anti‐'Mi a ' were 0·004% and 0·2%, respectively. Conclusion: The elimination of D typing of patients at MMH has proven to have been a correct and logical decision. D‐ patients, if they do not carry anti‐D, can thus be safely transfused with D+ red cells.